Harnessing molecular rotations in plastic crystals: a holistic view for crystal engineering of adaptive soft materials. (13th November 2020) - Das, Susobhan; Mondal, Amit; Reddy, C. Malla
Abstract : This review highlights the exceptional properties of plastic crystals, their expanding scope in materials sciences and plenty of opportunities for designing new mechanically soft functional crystals. Abstract : Plastic crystals (PCs), formed by certain types of molecules or ions with reorientational freedom, offer both exceptional mechanical plasticity and long range order, hence they are attractive for many mechano-adaptable technologies. While most classic PCs belong to simple globular molecular systems, a vast number of examples in the literature with diverse geometrical (cylindrical, bent, disk, etc. ) and chemical (neutral, ionic, etc. ) natures have proven their wide scope and opportunities. All the recent reviews on PCs aim to provide insights into a particular application, for instance, organic plastic crystal electrolytes or ferroelectrics. This tutorial review presents a holistic view of PCs by unifying the recent excellent progress in fundamental concepts from diverse areas as well as comparing them with liquid crystals, amphidynamic crystals, ordered crystals, etc. We cover the molecular and structural origins of the unique characteristics of PCs, such as exceptional plasticity, facile reversible switching of order-to-disorder states and associated colossal heat changes, and diffusion of ions/molecules, and their attractive applications in solid electrolytes, opto-electronics, ferroeletrics, piezoelectrics, pyroelectrics, barocalorics, magnetics, nonlinear optics, and so on. The recent progress not only demonstrates the diversity of scientific areas in which PCs are gaining attention but also the opportunities one can exploit using a crystal engineering approach, for example, the design of novel dynamic functional soft materials for future use in flexible devices or soft-robotic machines.